2017
DOI: 10.4236/health.2017.98089
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Autism Spectrum Disorders and Symptoms of Asthma, Allergic Rhinoconjunctivitis and Eczema among Japanese Children Aged 3 - 6 Years

Abstract: There is insufficient epidemiological evidence on the relationship between autism spectrum disorder (ASD) and allergic diseases. We performed a cross-sectional survey to elucidate the associations between them using validated screening tools. The participants were children aged 3 -6 years attending kindergarten or nursery school in Shika Town, Japan (n = 417; valid response rate = 80.4%). Autism spectrum features were scored on the Social Communication Questionnaire (SCQ). Allergic symptoms (asthma, allergic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Most previous studies investigated the association of a single allergic disorder, [15][16][17][31][32][33][34][35] or up to three allergic comorbidities, 14,23,24,26,30,36,37 and ADHD/ASD. To the best of our knowledge, the present study is the first study which enrolled children with up to six allergic comorbidities (Table 1) including drug allergy that was not previously studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies investigated the association of a single allergic disorder, [15][16][17][31][32][33][34][35] or up to three allergic comorbidities, 14,23,24,26,30,36,37 and ADHD/ASD. To the best of our knowledge, the present study is the first study which enrolled children with up to six allergic comorbidities (Table 1) including drug allergy that was not previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as was reported for allergic disorders, 2 genetic and environmental factors were shown to play a role in the pathogenesis of ADHD and ASD 10–13 . Indeed, several studies did investigate the association between allergic disorders and ADHD and/or ASD with controversial results 14–26 . Differences in size of the studies, follow‐up period, and diagnostic criteria, which were used in the various studies as well as the specific types of allergic disorders that were investigated, are most probably the causes for the conflicting reports.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies investigated the association of a single allergic disorder, [15][16][17][29][30][31][32][33] or up to three allergic comorbidities, 14,23,24,26,28,34,35 and ADHD/ASD. To the best of our knowledge, the present study is the first study which enrolled children with up to six allergic comorbidities (Table 1) including drug allergy that was not previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies did not find significant association between allergic disorders and the development of ADHD 15,17 or ASD, 25,29 . However, most studies that were done in different parts of the world provide evidence for high risk of pediatric allergic patients to develop ADHD 17,24,28,[30][31][32] or ASD 14,17,23,28,32 regardless to the ethnicity of the enrolled patients. A meta-analysis by Schans et al, 26 reported that asthma, rhinitis, and eczema were independent risk factors for ADHD development which is similar to our observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation